VD_FINDINFO Décision / 2012 / 665 vom 6. Juli 2012 - VD Tribunal cantonal (2012)
DÉFENSE NÉCESSAIRE, DROIT À UN DÉFENSEUR, DÉFENSE D'OFFICE, PEINE | 130 let. b CPP (CH), 132 al. 1 let. b CPP (CH), 132 al. 2 CPP (CH), 132 al. 3 CPP (CH)